(untitled) (Asian Education Studies, 2016)
In China, the latest issued national guideline for college English teaching in 2007 has set a significant agenda for college English teaching and learning in the changed context with enhanced objectives for teaching and learning, decentralised guideline for individual institution, innovated teaching and learning process and evaluation system, and particular concern for teacher professional development. This study starts with a contextual analysis of the implementation of the latest round of college English curriculum reform in mainland China, then presents an overview of the content of the new curriculum, and finally elaborates the changes brought by the reform to various aspects of college English teaching and learning. Implications and directions for future research are indicated in concluding remarks.